Two-Step Extraction of the Lower First Molar for Class III Treatment in Adult Patient - Kélei Cristina de Mathias Almeida; Ricardo Fabris Paulin; Taísa Barnabé Raveli; Dirceu Barnabé Raveli; Ary Santos-Pinto (Case Reports in Dentistry)
The aim of this article is to describe a case report of Class III malocclusion treatment with lower first molar extraction. The 27-year-old Caucasian male patient presented a symmetric face with a straight profile, hyperdivergent growth pattern, molar and cuspid Class III relation, and an anterior crossbite as well as a mild crowding on cuspids area, in both upper and lower arches and a tendency to posterior crossbite. The treatment was performed by the use of Haas expansion appliance followed by an initial alignment and leveling of the upper and lower arches with a fixed edgewise appliance, extraction of lower teeth aiming the correction of the incisors proclination and end the treatment with a Class I molar relationship. It resulted in a significant change in the patient’s profile, dentoalveolar Class III correction, upper arch expansion, leveling and alignment of the upper and lower arches, and improvement of tipping of the upper and lowers incisors. In cases of a dentoalveolar compensation in well positioned bone bases the treatment with fixed appliances is an alternative and extraction of lower teeth is considered.